(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the role of neologisms in improving the lexicology of English and Uzbek languages. Neologisms, or newly coined words, terms, and phrases, serve as indicators of linguistic evolution and cultural change. The main goal of this article is to study the mechanisms of neologisms contributing to the enrichment and expansion of the lexical reserves of both languages through a comparative analysis. For this purpose, the similarities and differences in the definition of neologisms in the English and Uzbek languages, their acceptance into the language, and the requirements for their adaptation to the language are highlighted through examples. . Finally, this article concludes by highlighting that the study of neologisms in language is an urgent topic that requires significant research within various fields of linguistics.